Tertiary Education in Sri Lanka: Issues and Challenges - N. Tharmaseelan (University of Sofia, 2007)
The paper reviews the contemporary issues and challenges faced by the Sri Lankan higher educational institutions and justify the need for immediate changes needed in the system. Based on survey conducted among the past graduates of Sri Lankan tertiary institution, it highlights the areas need improvement and suggests different models for various areas to enhance the quality in tertiary education.